Tuberculosis in the homeless population: social representations of Primary Health Care professionals (Research, Society and Development, 2021)
Objective: To understand the social representations of health professionals about Tuberculosis (TB) care in the Homeless Population (HP). Method: Exploratory and descriptive study, with a qualitative approach, conducted in Campina Grande - PB. The population consisted of higher education professionals from the Primary Health Care (PHC); 45 professionals agreed to take part in the research. For data collection, held between April and July 2017, semi-structured interviews were performed and questionnaires were completed. The interviews were analyzed with the aid of the Iramuteq software, through the Descending Hierarchical Classification. The analysis used the theoretical-analytical device of social representations. Results: The following classes were identified: Life on the streets: context of vulnerability; Challenges for the diagnosis and treatment of TB in HP; Obstacles to HP access to PHC; and The issue of the Street Clinic Team (SCT). Conclusion: Despite the recognition of the context of vulnerability, a series of barriers to HP access to PHC was noted. Concerning the actions and organization of services, representations that do not consider the specificities of HP prevailed. The performance of SCT was seriously undermined.